PENDAMPINGAN PENGEMBANGAN EKOWISATA DENGAN PENDEKATAN LINGKUNGAN DI EMBUNG PATEMON KECAMATAN GUNUNGPATI KOTA SEMARANG - Melati, Inaya Sari; Raeni, Raeni; Harnanik, Harnanik (Jurnal Terapan Abdimas, 2019)
Abstract. The objective of this service is the first to empower tourism Embung Patemon Kecamatan Gunungpati, Kota Semarang through the concept of ecotourism with an environmental approach. The second objective is to contribute positively to the existence of ecotourism empowerment with the environment approach in Embung Patemon, so that it can provide more value not only to the welfare of the local community, but also to environmental sustainability. The method of implementing community service activities in the form of empowerment and development of ecotourism for Embung Patemon with environmental approaches is carried out with training that produces skills, lecture methods, question and answer, discussion, simulation and mentoring. The results of community service activities that have been carried out are (1) The potentialof the village mapping and coordination activities, (2) identification of the potential of tourism in Embung Patemon as a basis for implementing ecotourism programs, (3) development of the potential tourism of Embung Patemon. The next stage of the plan is training in tourism marketing, evaluation of service programs, preparation of final service reports, and preparation and publication of articles / manuscripts to accredited national journals.Abstrak. Tujuan kegiatan pengabdian ini yang pertama adalah untuk memberdayakan wisata Embung Patemon Kecamatan Gunungpati, Kota Semarang melalui konsep ekowisata dengan pendekatan lingkungan. Tujuan kedua adalah memberikan kontribusi positif dari adanya pemberdayaan ekowisata dengan pendekatan lingkungandi Embung Patemon, sehingga mampu memberikan nilai lebih tidak hanya pada kesejahteraan masyarakat lokal, tetapi juga pada kelestarian lingkungan. Metode pelaksanaan kegiatan pengabdian kepada masyarakat berupa pemberdayaan dan pengembangan ekowisata Embung Patemon dengan pendekatan lingkungandilakukan dengan pelatihan yang menghasilkan keterampilan, metode ceramah, tanya jawab, diskusi, simulasi serta pendampingan. Hasil kegiatan pengabdian pada masyarakat yang telah terlaksana adalah (1) kegiatan kordinasi dan pemetaan potensi kelurahan, (2) identifikasi potensi wisata di Embung Patemon sebagai dasar dalam pelaksanaan program ekowisata, (3) pengembangan potensi wisata Embung Patemon. Rencana tahapan berikutnya adalah pelatihan pemasaran wisata, evaluasi program pengabdian, penyusunan laporan akhir pengabdian, serta penyusunan dan publikasi artikel/ manuskrip ke jurnal nasional terakreditasi.